The training process: Planning for strength-power training in track and field. Part 1: Theoretical aspects - DeWeese, B. H.; Hornsby, G.; Stone, M.; Stone, M. H. (Journal of Sport and Health Science, 2015)
The process of strength-power training and the subsequent adaptation is a multi-factorial process. These factors range from the genetics and morphological characteristics of the athlete to how a coach selects, orders, and doses exercises and loading patterns. Consequently, adaptation from these training factors may largely relate to the mode of delivery, in other words, programming tactics. There is strong evidence that the manner and phases in which training is presented to the athlete can make a profound difference in performance outcome. This discussion deals primarily with block periodization concepts and associated methods of programming for strength-power training within track and field.